Educational Innovation: Digital Learning in The Disruptive Era - Nugraheny, Devita Cahyani; Vioreza, Niken; Islahuddin, Islahuddin (PUSAKA: Journal of Educational Review, 2025)
Innovation is a process of renewal in all fields, one of which is education. With innovation, education can adapt itself to changes in society and technology, so that it can meet the demands of the times. This research aims to provide an in-depth overview of educational innovations applied in digital learning in a disruptive era. This research is descriptive qualitative research using the literature study method. The author uses various written sources such as articles, journals, and documents that are relevant to this study. The study results show that innovation is a process of renewal and change. The education sector needs innovation so that it can continue to develop and adapt to developments in other fields. Educational innovation in digital learning can involve various aspects of learning, including learning resources, learning media, learning evaluation, and platforms that support the learning implementation process.